Identification of Passenger Ship Accident Risk Management with Hazard and Operational Analyssis (HAZOP) Approach Riviewed From A Human Resources Perspevtive - Wahyuni, Anak Agung Istri Sri; Firdaus, Muhamad Imam; Ardhi, Eka Wahyu (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2025)
Passenger ship accidents are complex events resulting from multiple interrelated factors, with human error, technical deficiencies, and environmental conditions playing critical roles. Between 2018 and 2022, Indonesia’s National Transportation Safety Committee (KNKT) recorded 108 ship accidents, including 29 Ro-Ro passenger ships and 19 conventional passenger vessels. This study employs the Hazard and Operability Study (HAZOP) methodology to analyze risk factors contributing to passenger ship accidents, with particular emphasis on the human resource (HR) perspective. Primary data were collected through interviews and surveys with ship crew members, while secondary data were obtained from accident reports and maritime literature. The analysis identified key risks, including improper use of LPG stoves, unsafe cargo storage practices, malfunctioning fire detection systems, crew fatigue resulting from excessive workload, and vessel overloading. Each risk was systematically associated with specific mitigation measures through HAZOP analysis, translating human- and technical-related deviations into actionable safety recommendations. The findings underscore the importance of enhancing safety training, strengthening maintenance protocols, and improving HR management practices. The study concludes that reinforcing human factors, particularly through continuous safety training, scheduled maintenance, and more effective workload management, can significantly reduce the likelihood of accidents. Thus, this research not only identifies critical risk sources but also offers practical guidance for improving maritime operational safety and reducing incidents associated with human error.